Event Studies in Merger Analysis: Review and an Application Using U.S. TNIC Data - Timo Klein (Tinbergen Institute, 2020)
There is a growing concern that U.S. merger control may have been too lenient, but empirical evidence remains limited. After reviewing event studies as a method to acquire empirical insights into the competitive effects of mergers, I propose a novel application using Hoberg-Phillips TNIC data. This application allows for the ready approximation of abnormal stock market returns of likely competitors to 1,751 of the largest U.S. mergers since 1997. I document that likely competitors experience on average an abnormal return of close to one percent around a merger announcement. Abnormal returns are also strongly associated with concerns of market power, which suggests that competitors benefit at least in part because of an anticipation of anti-competitive effects – and hence insufficient merger control.
Keywords: G14; G34; L13; L40; 330; Mergers; Antitrust; Event Studies; Text-Based Network Industry Classification